1988
DOI: 10.1111/j.1469-7610.1988.tb00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead, Intelligence, Reading Attainment, and Behaviour in Eleven Year Old Children in Dunedin, New Zealand

Abstract: A study of blood lead levels and intelligence, reading, and behaviour problems was carried out using a sample of 579 Dunedin 11-yr-old children. The results suggested that when account was taken of social, environmental, and background factors, raised blood lead is associated with a small but statistically significant increase in children's general behaviour problems as reported by both parents and teachers. These results applied especially to the more specific problems of inattention and hyperactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
3
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 9 publications
5
54
3
1
Order By: Relevance
“…Compared with the more powerful impact of social factors, such changes in behavior are likely to be of minimal clinical significance. The small amount of total variance in behavior problems explained in this and other studies 12 underscores that other, unmeasured, factors contribute more substantially to behavioral outcomes.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Compared with the more powerful impact of social factors, such changes in behavior are likely to be of minimal clinical significance. The small amount of total variance in behavior problems explained in this and other studies 12 underscores that other, unmeasured, factors contribute more substantially to behavioral outcomes.…”
Section: Discussioncontrasting
confidence: 40%
“…As is typical in studies of childhood lead exposure, blood lead was log transformed (natural log) owing to its skewed distribution. For each subscale, a regression analysis was conducted for each blood sampling time point (umbilical cord and at 6,12,18,24,30, and 36 months). In each case, sociodemographic variables (town, residence type, child's sex and ethnicity, maternal education, and sum of the 2 HOME subscales) were first entered together.…”
Section: Data Analysesmentioning
confidence: 99%
“…In the Mexican cross-sectional study using blood as the measure of lead exposure, increased lead body burden was associated with decreased knowledgeability and socialization skills on a teacher's rating scale, as well as impaired performance on the WISC-R (36). In the Scottish cross-sectional study with blood lead as the independent variable (37), a dose-related increase on the aggressive/antisocial and hyperactive measures of the Rutter scale was observed in a group of 6-to 9-year-old children with low blood lead levels, who also exhibited a dose-related decrease in IQ (38) cross-sectional study in Dunedin, New Zealand, significant associations were found between blood lead levels and increased behavioral problems, as assessed by both teachers and parents on the Rutter Behavioral Scale, and increased scores on inattention and hyperactivity scales in the absence of changes in IQ (42). In the Boston prospective study (49), behavior was assessed by a teacher's rating scale when the children were 8 years old.…”
Section: Human Studiesmentioning
confidence: 97%
“…15 Two studies examined children screened for disruptive behavior problems and found associations between elevated lead levels and behavior problems. [41][42] However, because these studies did not assess ADHD, the extent to which their findings may be applied to children with this http://www.pediatrics.org/cgi/content/full/107/3/e43disorder is unknown. These findings suggest an association between elevated lead levels and a range of behavior problems including inattention.…”
Section: Medical and Laboratory Screening Testsmentioning
confidence: 99%